A psychological flexibility conceptualisation of the experience of injustice among individuals with chronic pain - Scott, Whitney (Br J Pain, 2014)
Accumulating evidence suggests that the experience of injustice in patients with chronic pain is associated with poorer pain-related outcomes. Despite this evidence, a theoretical framework to understand this relationship is presently lacking. This review is the first to propose that the psychological flexibility model underlying Acceptance and Commitment Therapy (ACT) may provide a clinically useful conceptual framework to understand the association between the experience of injustice and chronic pain outcomes. A literature review was conducted to identify research and theory on the injustice experience in chronic pain, chronic pain acceptance, and ACT. Research relating injustice to chronic pain outcomes is summarised, the relevance of psychological flexibility to the injustice experience is discussed, and the subprocesses of psychological flexibility are proposed as potential mediating factors in the relationship between injustice and pain outcomes. Application of the psychological flexibility model to the experience of pain-related injustice may provide new avenues for future research and clinical interventions for patients with pain. SUMMARY POINTS: • Emerging research links the experience of pain-related injustice to problematic pain outcomes. • A clinically relevant theoretical framework is currently lacking to guide future research and intervention on pain-related injustice. • The psychological flexibility model would suggest that the overarching process of psychological inflexibility mediates between the experience of injustice and adverse chronic pain outcomes. • Insofar as the processes of psychological inflexibility account for the association between injustice experiences and pain outcomes, methods of Acceptance and Commitment Therapy (ACT) may reduce the impact of injustice of pain outcomes. • Future research is needed to empirically test the proposed associations between the experience of pain-related injustice, psychological flexibility and pain outcomes, and whether ACT interventions mitigate the impact of pain-related injustice on pain outcomes.